Analysis of proteasomal proteolysis during the in vitro metacyclogenesis of Trypanosoma cruzi. - Josiane Cardoso; Carla De Paula Lima; Tiago Leal; Daniela F Gradia; Stênio P Fragoso; Samuel Goldenberg; Renata Guerra De Sá; Marco A Krieger (PLoS ONE, 2011)
Proteasomes are large protein complexes, whose main function is to degrade unnecessary or damaged proteins. The inhibition of proteasome activity in Trypanosoma cruzi blocks parasite replication and cellular differentiation. We demonstrate that proteasome-dependent proteolysis occurs during the cellular differentiation of T. cruzi from replicative non-infectious epimastigotes to non-replicative and infectious trypomastigotes (metacyclogenesis). No peaks of ubiquitin-mediated degradation were observed and the profile of ubiquitinated conjugates was similar at all stages of differentiation. However, an analysis of carbonylated proteins showed significant variation in oxidized protein levels at the various stages of differentiation and the proteasome inhibition also increased oxidized protein levels. Our data suggest that different proteasome complexes coexist during metacyclogenesis. The 20S proteasome may be free or linked to regulatory particles (PA700, PA26 and PA200), at specific cell sites and the coordinated action of these complexes would make it possible for proteolysis of ubiquitin-tagged proteins and oxidized proteins, to coexist in the cell.